Europa, España: crisis, industria, educación y solidaridad - Garrido, José Antonio (Revista Española de Pedagogía, 2018)
This paper deals with subjects that are of essential concern to European and Spanish industries, and in doing so, it does not overlook social solidarity. In these stormy, crisis ridden times, recipes that applied to our more peaceful times are no longer of any practical use. This all calls for a change in the relationship between the individual and the organization. A new moral contract emerges, where the employee will not necessarily find that his loyal dedication is always rewarded by his being given a full time job for life. It will rather lead to conditions that allow continuous employability on an individual basis. The new concept of the social Europe takes solidarity as a down-to-earth condition for overcoming the crisis, instead of regarding it as support for conditions which may not be sympathethic towards today¿s new realities. There is a need for competitiveness to be restored in European industry, but that competitiveness must be made to be compatible with the social and economic cohesion that characterises the European growth model.
Keywords: España; Europa; crisis; industria; educación; solidaridad; Revista Española de Pedagogía